Landsnails (Gastropoda) in Tam Dao national park, Vinh Phuc province, Vietnam - Khac, Hoang Ngoc; Nhuong, Do Van; Cay, Nguyen Thi; Nhat, Tran Thap (Academia Journal of Biology, 2012)
The survey and sampling land snails in Tam Dao National Park were conducted from 2003 to 2011. We have identified 52 species and subspecies of terrestrial gastropods in Tam Dao, belonging to 31 genera, 13 families and 2 orders (Architaenioglossa, Stylommatophora), 2 subclass (Prosobranchia, Pulmonata). Of all families recorded: Cyclophoridae, Pupinidae, Subulinidae, Camaenidae, Bradybaenidae, Ariophantidae, Helicarionidae, Plectopylididae, Clausiliidae, Achatinellidae, Streptaxidae, Streptaxidae and Achatinidae,  the family Cyclophoridae is the most abundant in number of species (up 19.23% of the total species), the Clausiliidae occupied the second place with 13.4% of the total species, and all the rest of families are less. The species of large size, widely distributed in many parts of northern Vietnam are Camaena vaysieri, Cyclophorus songmaensis, Cyclophorus siamensis and Cyclophorus exaltus, the tiny-sized species are Videna timorensis, Pupina anceyi and Pupina brachysoma. In habitat, the most abundant species are observed in natural forest, then in edge of forest, and least of all in cultivated land and wasteland. In surveying lines, the residential district of Tam Dao has the most abundant species. The dominant species in natural forest habitats belong to the families Ariophantidae and Helicarionidae, the common species widely distributed belong to the family Bradybaenidae, such as Bradybaena jourdyi, Bradybaena similaris. The dominant species in cultivated land belong to the families Clausiliidae and Subulinidae, a Achatina fulica is considered as an exotic species.